Biomechanics of Vertical Posture and Control with Referent Joint Configurations. Issue 1 (2nd January 2021) - Yamagata, Momoko; Gruben, Kreg; Falaki, Ali; Ochs, Wendy L.; Latash, Mark L.
Abstract: Our study compared the results of two methods of analysis of postural sway during human quiet standing, the rambling-trembling ( Rm - Tr ) decomposition and the analysis of the point of intersection of the ground reaction forces ( zIP analysis). Young, healthy subjects were required to stand naturally and with an increased level of leg/trunk muscle co-activation under visual feedback on the magnitude of a combined index of muscle activation (muscle mode). The main findings included the shift of zIP toward higher frequencies and strong correlations between Tr and zIP when the subjects stood with increased muscle co-activation. We interpret the results within the idea of whole-body control with a set of primitives associated with referent coordinates in the joint configuration space.